Gradient material Pd-PdHx - M. V. Goltsova; I. G. Zhirov; D. A. Nazarov (Литьë и металлургия)
There was analyzed videotape recording of palladium plate bending during its one-side saturation with hydrogen in experimental conditions of isothermal temperature 130 °С, step hydrogening up to РН2 = 0,01 МPа, 0,033, 0,05 МPа. For experiments pure palladium plate of (68×5,5×0,27) mm size electrolytically covered with copper was used as well as specially constructed hydrogen vacuum device. It is shown, that palladium plate bending processes in two stages. In the first stage it is very intensive and quickly reaches values much more than plates thickness. In the second stage the plate is returning to initial state but fixing a small residual form changing. The second stage is much more slow than the first one. Repeated hydrogening lead to a decrease in the maximum bending of the plate. It is shown that the bending is caused by internal stresses induced by hydrogen concentration gradients but the responsibility of such a behavior possessed by temporarily existing gradient material Pd-PdHx. In the first moments of saturation the layer of PdHx is formed in palladium subsurface layers and a side near copper is free from hydrogen. As hydrogen concentration in plate becomes equal through the plate thickness, the plate returns to initial form.There were calculated parameters of temporarily existing gradient material Pd-PdHх in frames of model discussed. Results of the work are of interest for development of hydrogen sensors.